دراسة مقارنة لقوة العضة بالأجهزة التعويضية الكاملة قبل وبعد تبطينها - لايقة, عمار (Latakia University Journal -Medical Sciences Series, 2019)
تعتبر قوة العضة الأعظمية مؤشراً يعكس الحالة الوظيفية للأجهزة التعويضية الكاملة. إن هدف هذه الدراسة هو تقييم إمكانية تحسن قوة العضة عند حملة الأجهزة التعويضية الكاملة، وذلك بعد تبطينها بمواد مبطنة مختلفة: 1- مادة لدنة مؤقتة ذات أساس سيليكوني 2- مادة قاسية مؤقتة ذات أساس أكريلي 3- مادة قاسية دائمة ذات أساس أكريلي. أجريت الدراسة على ثمانين مريضاً وذلك باستخدام أداة الغناتوميتر (Gnathometer, blend-a-dent, procter & Gamble) لقياس قوة العضة قبل المعالجة ثم مباشرة بعد تبطين الجهاز التعويضي الكامل بالمواد السابقة المختلفة ثم بعد أسبوع من تبطين الجهاز. تمت إعادة كل قياس ثلاث مرات في ثلاث مناطق مختلفة (القواطع، الأرحاء الأولى اليمنى واليسرى). أظهرت النتائج تحسناً كبيراً في قوة العضة لدى المرضى خلال الأسبوع الأول من تبطين الأجهزة الكاملة لديهم بمواد التبطين المختلفة (p < 0.05)، وقد كان التحسن في قوة العضة أعظمياً لدى المرضى، وذلك مباشرة بعد تبطين أجهزتهم التعويضية بمادة التبطين المؤقتة اللدنة. يمكن أن نستخلص من هذه النتائج أن تبطين الأجهزة التعويضية الكاملة يؤدي إلى زيادة في قوة العضة عند هؤلاء المرضى، لاسيما عند تبطينها بمواد تبطين لدنة ذات أساس سيليكوني أكثر من الأجهزة الكاملة عند تبطينها بمواد قاسية ذات أساس أكريلي نتيجة لزيادة ثباتها وتحسين حالتها الوظيفية. The maximum bite force is often said to reflect the functional status of complete dentures. The aim of this study was to evaluate if and to which extend the maximum bite force of ill-fitting complete dentures can be increased by relining the dentures with different methods and materials: 1. Soft immediate material of acrylic basis. 2. Hard immediate material of acrylic basis. 3.Permanent material of acrylic basis. The measurements were performed on 80 patients with a newly developed instrument (Gnathometer, blend-a-dent, procter & Gamble) before treatment (baseline) and immediately after insertion of the relined denture. Additional records were made after one week respectively. Each measurement was repeated three times in three different areas, e.g. incisor region, right and left first molar region. Results indicate that there is a high significant increase (p < 0.05) in bite force within the first week after relining the dentures with the different materials. Furthermore, it is remarkable that the greatest amount of the increase of bite force developed immediately after inserting the dentures which relined with soft lining material. The study concludes that there is evidence to believe that optimizing dentures by relining them with soft lining materials of silicone basis, gives positive results with complete denture wearers, and is better than results of hard lining material of the acrylic basis; and therefore positively affects the functional status of complete dentures.